Biomechanical report for the IAAF World Indoor Championships 2018 60m men - Walker, J.; Tucker, C.; Paradisis, G.; Bezodis, I.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The men`s 60 m sprint took place on the evening of Saturday 3rd March. The overwhelming favourite going into the event was Christian Coleman of the United States, having broken the World Indoor Record by 0.05 s only two weeks prior to the championships. Coleman had also been consistently performing extremely well throughout the indoor season. Other finalists such as Ronnie Baker (United States) and Su Bingtian (China) had also been performing well so were in contention for a medal but would have been hoping to cause an upset. In the end, Coleman dominated the race. His time of 6.37 s resulted in a new Championship record being set, which had previously stood for almost 20 years. Su Bingtian claimed the silver medal with a time of 6.42 s, which was a new Area Indoor Record. Ronnie Baker took the bronze medal in 6.44 s.